2019
DOI: 10.1136/gpsych-2019-100075
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of psychosis induced by interferon alpha and ribavirin with paliperidone: first case reported

Abstract: Several clinical studies have shown a large number of mental symptoms by immunomodulatory treatment with interferon (IFN). The most frequently described symptoms are depression, suicidal behaviour, manic symptoms, anxiety, psychosis and delirium, associated with other non-specific symptoms such as fatigue, irritability, psychomotor retardation, decreased libido, insomnia, difficulty in concentration and attention. Having a history of mental disorder contraindicates the use of IFN-alpha. These adverse effects t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
0
6
0
1
Order By: Relevance
“…Several reports have revealed no significant differences between schizophrenia and controls in terms of plasma IFN-α levels ( 23 , 24 ). However, from a clinical point of view, it has been known that IFN-α treatment is strongly associated with mental symptoms such as depression and psychosis ( 25 , 26 ). Thus, elevated endogenous IFN-α levels in the chronic phase of schizophrenia may be the common biological change that causes depression.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have revealed no significant differences between schizophrenia and controls in terms of plasma IFN-α levels ( 23 , 24 ). However, from a clinical point of view, it has been known that IFN-α treatment is strongly associated with mental symptoms such as depression and psychosis ( 25 , 26 ). Thus, elevated endogenous IFN-α levels in the chronic phase of schizophrenia may be the common biological change that causes depression.…”
Section: Discussionmentioning
confidence: 99%
“…It is known to have minimal hepatic metabolism [ 3 ]. It is a drug that is well tolerated in patients with impaired hepatic function and does not have metabolic drug interactions [ 9 ].…”
Section: Reviewmentioning
confidence: 99%
“…So, schizophrenia should not stop a person from taking anti-viral therapy when infected with the hepatitis C virus [ 11 ]. A case report by Carrillo de Albornoz Calahorro et al [ 9 ] evaluated the treatment preferred in patients suffering from psychosis due to interferon and ribavirin therapy (used for viral hepatitis). They concluded that since most antipsychotics are metabolized by the liver, a drug that has the least hepatic metabolism should be preferred so that there is the least possible hepatic damage.…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations